Analisis Konten Pesan Komunikasi Akun Instagram BKKBN - Olih Solihin; Fajar Adi; Zikri Fachrul Nurhadi; Muslim Muslim (Alhadharah: Jurnal Ilmu Dakwah, 2022)
Communication messages on the BKKBN Instagram account are important to meet the information needed by the community regarding the Family Planning Program (FP). This study aims to describe the message target, intended target, message content and message reference on the BKKBN Instagram account. Stimulus, Organism and Response (SOR) Theory as the grand theory used in this study, provides an overview of the effect (response) of the message (stimulus) which is the subject of this research. This research is a quantitative descriptive research with content analysis method. Based on the results of descriptive analysis, it is known that most of the target messages on the BKKBN Instagram account aim to provide information, with the intended target mostly being addressed to the general public, and the message content is more about knowledge for the intended target, while message references tend to be without references or come from media team creative. Taking into account the element of the message (stimulus) that is conveyed through the BKKBN Instagram account, it is recommended that the BKKBN Instagram account more direct its targets to the millennials generation or even to the zillennials generation, most of whom are currently entering the age of marriage and also paying more attention to the source of the uploaded message reference.